Optimasi Decision Support System (DSS) Pemilihan Paket Layanan Internet Prabayar Dengan Metode ANP - Azhar, Asbon Hendra; Destari, Ratih Adinda (STIKOM Tunas Bangsa Pematangsiantar, 2019)
At this time there are so many Internet packages provided by companies in the telecommunications sector to help facilitate Android users in accessing the Internet. Android users using this Internet package are for the purposes of social media, chatting, browsing, streaming and downloading where Android users will feel incomplete if they do not use the Internet package because in terms of finance it is most cost effective compared to using regular pulses. The Internet is currently one of the main alternatives in meeting all needs, namely Information and Education needs that provide positive value for all people. The number of operators offering Internet packages will certainly make it difficult for consumers to make the right choice according to their wishes and criteria. To overcome these problems, a system is made that will make decision making easier for choosing an Internet service package, one of which is the decision support system to help the community choose the best Internet service package. The method used in this study is the ANP Method. With the ANP method, it is expected to help the community in determining which alternatives will be chosen as a final decision in the selection of Internet Packages as needed